Technical Development and Agricultural Policy - Dimény, Imre (Acta Agraria Debreceniensis, 2002)
Summarising a study work taken several decades four highly important fields are discussed in this essay:- theoretical and practical methods of technical development,- some special character of the technical development-friendly economic environment,- specialities of the present situation,- preliminary hopes for the future.